Integrating Poda Na Lima: A Cultural Framework for Menstrual Hygiene Management Education among Batak Women in Indonesia - Masrina Munawarah Tampubolon; Sakinah Yusro Pohan; Cory Linda Futri (Jurnal Ners, 2026)
Menstrual hygiene management (MHM) remains a critical concern among adolescent girls in Indonesia, particularly within cultural settings where traditional wisdom shapes health behaviors. This study explored how Poda Na Lima as a Batak moral philosophy emphasizing spiritual, physical, and environmental cleanliness serves as a culturally grounded framework for menstrual hygiene education. Using a phenomenological qualitative design, data were gathered through in-depth interviews and focus group discussions with mothers from the Angkola, Mandailing, and Toba ethnic groups in Padangsidimpuan, Indonesia. Data were analyzed using Colaizzi’s method. Two overarching themes emerged: (1) mothers’ perceptions of Poda Na Lima as a philosophical foundation for health education, represented by the subtheme Poda Na Lima as a guideline for clean and healthy living; and (2) mothers’ methods of delivering MHM education, encompassing four interrelated subthemes—instilling menstrual hygiene awareness, serving as role models, demonstrating hygiene practices, and evaluating daughters’ practices. These findings indicate that Poda Na Lima functions not only as a moral code but also as an indigenous pedagogical approach through which mothers transmit menstrual hygiene values. The study highlights the importance of integrating cultural wisdom into reproductive health education to improve menstrual literacy and sustain behavior change among Batak communities in Indonesia. Keywords: Culturally grounded intervention, Health literacy, Menstrual Hygiene Management (MHM), Poda Na Lima, Reproductive health education